2013
DOI: 10.1128/mbio.00385-13
|View full text |Cite
|
Sign up to set email alerts
|

A Short Hairpin RNA Screen of Interferon-Stimulated Genes Identifies a Novel Negative Regulator of the Cellular Antiviral Response

Abstract: The type I interferon (IFN) signaling pathway restricts infection of many divergent families of RNA and DNA viruses by inducing hundreds of IFN-stimulated genes (ISGs), some of which have direct antiviral activity. We screened 813 short hairpin RNA (shRNA) constructs targeting 245 human ISGs using a flow cytometry approach to identify genes that modulated infection of West Nile virus (WNV) in IFN-β-treated human cells. Thirty ISGs with inhibitory effects against WNV were identified, including several novel gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 49 publications
4
109
0
Order By: Relevance
“…Early studies attempting to evaluate the antiviral function of IFI6-16 showed that introduction of IFI6-16 in a KO cell line (HT1080_IFI6 −/− ) does not affect the replication of encephalomyocarditis virus, Semliki forest virus, or coccal virus, suggesting that IFI6-16 is not required to control these viral replications (61). In contrast, IFI6-16 was identified as a negative regulator that markedly inhibited the replication of yellow fever virus (31), DENV (62), and West Nile virus (63). The expression of the gene was also found to suppress respiratory syncytial virus replication and was down-regulated by the virus (64).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies attempting to evaluate the antiviral function of IFI6-16 showed that introduction of IFI6-16 in a KO cell line (HT1080_IFI6 −/− ) does not affect the replication of encephalomyocarditis virus, Semliki forest virus, or coccal virus, suggesting that IFI6-16 is not required to control these viral replications (61). In contrast, IFI6-16 was identified as a negative regulator that markedly inhibited the replication of yellow fever virus (31), DENV (62), and West Nile virus (63). The expression of the gene was also found to suppress respiratory syncytial virus replication and was down-regulated by the virus (64).…”
Section: Discussionmentioning
confidence: 99%
“…Mx1, PKR, RNase L, and OAS) [26,27]. One of the key recent advances in our understanding of host factors that restrict WNV (as well as many other viruses) has been the application of large-scale ectopic expression [28,29] or gene silencing [30,31] screens to identify sets of genes that control viral replication in vitro . Such approaches have detected previously described components of the antiviral response (e.g.…”
Section: Genetic Screens Identify Ifn-induced Antiviral Effector Molementioning
confidence: 99%
“…MAVS engagement coordinates the activation of NF-kB and IRFs through the IKK and IKK-related kinases, respectively, resulting in the assembly of the IFNb (Ifnb) enhancesome and subsequent gene induction (McWhirter et al, 2005). IFNb, a type I IFN (IFN-I), leads to upregulation of hundreds of IFN-stimulated genes (ISGs), which together cooperate to slow virus replication (Li et al, 2013;Schoggins et al, 2011).…”
Section: Introductionmentioning
confidence: 99%